Null subjects in european and Brasilian Portuguese - Barbosa, Pilar (2005)
The goals of this paper are twofold: a) to provide a structural account of the effects of the informal ‘Avoid Pronoun Principle’, proposed in Chomsky (1981: 65) for the Null Subject Languages (NSLs), and b) to compare, in European and Brazilian Portuguese (EP and BP), the distribution of the third person pronouns in its full and null forms, to check whether in written corpora BP incorporates signs of the ongoing loss of the null subject, largely attested in its contemporary spoken language. The strong theoretical claim is that in the Romance non-NSLs the pre-verbal subject is sitting in Spec of IP, while in the Romance NSLs it is Clitic Left-Dislocated (or is extracted by A-bar movement if it belongs to a restricted set of non-referential quantified expressions). The paper provides quantitative evidence that BP is losing the properties associated with the Null Subject Parameter. In its qualitative analysis, it shows that the contrasts between EP and BP are easily accounted for if the two derivations are assumed and if the null subjects in the two varieties are considered to be of a different nature: a pronoun in EP and a pronominal anaphor in BP.